The Symbolic Violence In “Imperfect” (Pierre Bourdieu's Review of Critical Discourse Analysis) - Yunus Khoirul Amal; Prasetyo Adi Wisnu Wibowo; Titis Srimuda Pitana (International Journal of Science and Applied Science: Conference Series, 2022)
The film "Imperfect" (2019) is an Indonesian film that tells the story of the pressure in women's lives related to their body shape. A woman's body that does not conform to developing standards will be pressured to conform to existing standards. Symbolic violence that occurs against women is happening nowadays, and society considers beauty to have an ideal physique, regardless of one's qualities, but women who have an ideal physique are more valued and more attractive. This study used descriptive qualitative method. The data collection technique used is observation on imperfect films. To answer this problem, the researcher uses the theoretical approach of critical discourse analysis and symbolic violence from Pierre Bourdieu. The results showed that; 1) discourse about women who have an ideal body, have white skin, are tall, and have straight hair are always considered as women who deserve attention and always get their own privileges; 2) Discourse related to the standard of beauty for women has developed and can lead to symbolic violence because women who do not meet the standards of beauty set above will always be marginalized and compared as a form of symbolic violence.